Faktor-faktor yang Berhubungan dengan Penyembuhan Luka Post Sectio Caesarea di RSUD Arifin Achmad Provinsi Riau Tahun 2013 - Ika Putri Damayanti (STIKes Hang Tuah Pekanbaru, 2014)
Post Sectio Caesarea wound is a wound that made an impression and is caused by cesarean when a woman can not give birth main normal. Prinsip in wound care is the control of infection because infection can inhibit wound healing, causing morbidity and mortality increase. This study aims to determine the factors associated with wound healing post sectio caesareadi Arifin Achmad Riau Province in 2013. This research is quantitative research using cross sectional study design. The location of research is Arifin Achmad Riau Province, the research was conducted in October-May 2014. The population in this study is the status of the mother's Medical Record sectio caesarea in 2013 amounted to 910 people with a sample of 154 people. Systematic sampling technique is random sampling. The data used in this research is secondary data is data mothers delivered in SC, age, mother of data with infection and disease history data. Data analysis for bivariate with Chi-Square test. The results show for the factors associated with wound healing post sectio caesarea is variable risk age 79 (51.3%), OR = 2.91 (95% CI: 1.50 to 5.65), maternal variables 83 infections (53.9%), OR = 6.59 (95% CI: 3.24 to 13.41), and a mother who suffered variables Diabetes 80 (51.90%), OR = 3.06 ( 95% CI: 1.57 to 5.94). The conclusion of this study is that there is a relationship of age, infection and diabetes mellitus with wound healing post sectio caesarea. Expected to health professionals in order to further improve the education and information about wound care operations, and better monitor the healing of wounds with age and history of diabetes mellitus yan suffered by the patient.